2016
DOI: 10.18632/oncotarget.11876
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the Hippo pathway transcriptional coactivators YAP/TAZ and β1-integrin in conventional osteosarcoma

Abstract: IntroductionCurrently, very few studies are available concerning the mammalian Hippo pathway in bone sarcomas. YAP/TAZ transcription co-activators are key downstream effectors of this pathway and may also have oncogenic properties. Additionally, recent in-vitro experiments showed that expression of β1-integrin promoted metastasis in osteosarcomas. This study investigated the expression of YAP/TAZ and β1-integrin in human osteosarcomas.Materials and methodsWe performed automated immunohistochemistry on tissue-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 32 publications
6
41
1
Order By: Relevance
“…The lack of association in our study may be because of the small sample size. A recent study found that YAP/TAZ immunoreactive score was correlated with overall survival of osteosarcoma patients . Among the five mesothelioma cell lines we studied, three (211H, H2052 and H290) showed both decreased phosphorylation of YAP (Ser127) to YAP ratio and increased GTIIC reporter activity.…”
Section: Discussionmentioning
confidence: 86%
“…The lack of association in our study may be because of the small sample size. A recent study found that YAP/TAZ immunoreactive score was correlated with overall survival of osteosarcoma patients . Among the five mesothelioma cell lines we studied, three (211H, H2052 and H290) showed both decreased phosphorylation of YAP (Ser127) to YAP ratio and increased GTIIC reporter activity.…”
Section: Discussionmentioning
confidence: 86%
“…Immunohistochemically, high YAP expression was noted in 60% to 85% of osteosarcomas [184][185][186][187], but only nuclear immunoreactivity in 30% to 46% of cases correlated with an adverse outcome (observed in some [184,185] but not all studies, potentially due to small patient cohorts [186,188]). Metastatic events were either not [186] or only slightly more frequent in patients with nuclear YAP (53%) than in those lacking nuclear YAP immunoreactivity (36%) [185].…”
Section: Yap/taz In Osteosarcomamentioning
confidence: 98%
“…Literature on OS is less scarce than on EWs. Aberrations in Hippo signaling pathway were demonstrated in OS using immunochemistry approaches; this demonstrated a nuclear localization of YAP in OS patient tumor biopsies [90,91]. Interestingly, Bouvier and Coll have proven a correlation between YAP nuclear localization and a poor prognosis, allowing for the establishment of a vital prognostic at diagnosis [90].…”
Section: Osteosarcomamentioning
confidence: 99%